Konsep Pola Industri dan Perusahaan - Ni Made Arsita Kusumadewi; Miftahul Hariz; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The research findings indicate that industrial patterns have a significant impact on companies, both positively and negatively. This study is expected to provide a better understanding for companies in facing changes in industrial patterns, thereby enhancing performance and competitiveness in fluctuating markets. The objectives of this research are: 1. To understand the relationship of industrial patterns/structure with the market.2. To identify the elements of industrial structure within the market.3. To determine the role of industrial patterns for companies.